Faktor – Faktor yang Mempengaruhi Kinerja Karyawan pada PT. Blue Bird Pool Garuda - Syahdina, Aang; Laing, Muhammad Rezal; Fitria, Amanda Putri; Maharani, Sephia; Septiani, Neli; Witantris, Rahma Maulidda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study seeks to empirically examine the impact of stress, motivation, and workload on the performance of employees at PT Blue Bird Pool Garuda. This study employs a quantitative methodology, relying on primary data for analysis. The sample consists of 100 employees selected through a saturated sampling method, or census. Data collection was conducted using questionnaires distributed to the employees, and the analysis was performed using SmartPLS V.4.0 software within the SEM framework. The findings reveal that, while work stress and workload individually do not have a significant effect on employee performance, motivation has a significant positive impact on performance.